Pengaruh Kredit Usaha Rakyat, Nilai Output, dan Pendidikan terhadap Penyerapan Tenaga Kerja Industri Mikro di Indonesia - Firdaus Apriliana (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of People's Business Credit (KUR), output value, and education on labor absorption in Indonesia's micro industry sector. Using panel data regression with the Fixed Effect Model approach, this study covers 34 provinces during 2017-2024. Secondary data were obtained from the Central Bureau of Statistics and the Coordinating Ministry for Economic Affairs. The results show that KUR has a negative and significant effect on labor absorption, while output value has a positive and significant effect. Education has a positive but not significant effect. The Adjusted R² of 0.9855 indicates that 98.55% of labor absorption variation is explained by the three independent variables. This study contributes to understanding labor absorption determinants and provides implications for government policies in expanding employment opportunities